Study of the effect of Nigella sativa seeds and Oleo european leaves on white rats fed a high fat and high sucrose diet - Rahma Al-Hammali, Hanaa Almabrouk, Khadiga Mohammed, Medhma Aburmel and Halima Ali (Journal of Pure & Applied Sciences, 2018)
The aim of this study was to determine the effects of the powders of Nigella sativa seeds (NSS) and Oleo european leaves (OEL) on blood glucose and blood lipid in high sucrose and high fat diet (HSFD) fed white male rats after nine weeks of administration. 24 of white male rats were divided into four groups each with 6 rats. At the end of this study there were an increase in Fast Blood Glucose (F.B.G.), Total Cholesterol (TC), Triglycerides (TG) and Low Density Lipoprotein-Cholestrol (LDL-Chol)  levels and a decrease in High Density Lipoprotein- Cholestrol (HDL-Chol), all changes were significant except TC in HSFD fed animals. The administration of NSS causes a decrease in F.B.G., TC, TG and LDL-Chol and an increase in HDL-Chol levels, and all changes were significant except F.B.G and TC. The administration with OEL causes a decrease in F.B.G., TC, TG, LDL-Chol and HDL-Chol levels. All changes were significant except F.B.G.